Modul Pembelajaran Untuk Siswa Madrasah Ibtidaiyah Di Lingkungan Guru–Guru Kota Bengkulu - Johanes Sapri; Nesna Agustriana (Institut Agama Islam Negeri Bengkulu, 2022)
Abstract: Learning Module for Elementary School Students in the Bengkulu City Teachers' Environment.The purpose of this study was to provide knowledge and skills in preparing Learning Modules for Elementary School Students in Bengkulu City Teachers' Environment. The research model used in this training is participatory training through several approaches, including; identification of needs, such as problem recognition, needs and potential of the school environment and school area and community. Applied training and learning techniques; Group work analyzes and synthesizes from theory and presentation results of instructors in classes related to the Preparation of Learning Modules for Madrasah Ibtidaiyah (MI) Students in the Bengkulu City Teachers' Environment. The training participants totaled 34 teachers. The output of this training is to produce a product in the form of a Learning Module for Elementary School Students in the Bengkulu City Teachers' Environment based on an analysis of students' learning needs in subjects; good scientific publications published in journals. The design of teaching materials is recommended to have a potential assessment and prioritization of problems faced by students in learning in each subject that is relevant to learning objectives, materials, methods, tools and media, as well as learning evaluation. Abstrak: Modul Pembelajaran Untuk Siswa Madrasah Ibtidaiyah Di Lingkungan Guru–Guru Kota Bengkulu.Tujuan penelitian ini adalah untuk memberikan pengetahuan dan keterampilan dalam penyusunan Modul Pembelajaran Untuk Siswa Madrasah Ibtidaiyah di Lingkungan Guru-Guru Kota Bengkulu. Model penelitian yang digunakan pada pelatihan ini adalah pelatihan partisipatif melalui beberapa langkah pendekatan, diantaranya; identifikasi kebutuhan, seperti pengenalan masalah, kebutuhan dan potensi lingkungan sekolah dan wilayah sekolah dan masyarakat. Teknik Pelatihan dan pembelajaran yang diterapkan; Kerja kelompok menganalisis dan mensintesis dari teori dan hasil presentasi para Instruktur di kelas yang berhubungan dengan Penyusunan Modul Pembelajaran Untuk Siswa Madrasah Ibtidaiyah (MI) di Lingkungan Guru-Guru Kota Bengkulu. Peserta pelatihan berjumlah berjumlah 34 orang guru. Luaran Pelatihan ini adalah menghasilkan produk berupa Modul Pembelajaran Untuk Siswa Madrasah Ibtidaiyah di Lingkungan Guru-Guru Kota Bengkulu berdasarkan analisis kebutuhan belajar siswa dalam mata pelajaran; publikasi ilmiah baik yang dipublikasikan di jurnal. Rancangangan bahan ajar dianjurkan memiliki pengkajian potensi dan penetapan prioritas masalah yang dihadapi siswa dalam pembelajaran pada setiap mata pelajaran yang relevan dengan tujuan pembelajaran, materi, metode, alat dan media, serta evaluasi pembelajaran.